1989
DOI: 10.1111/j.1365-2621.1989.tb07931.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Enzymatic Browning in Apple with Ascorbic Acid Derivatives, Polyphenol Oxidase Inhibitors, and Complexing Agents

Abstract: Novel browning inhibitors were evaluated in raw apple juice and on the cut surface of apple plugs, using quantitative measurements of color changes during storage to assess treatment effectiveness. Ascorbic acid-2-phosphate (AAP) and -triphosphate (AATP) showed promise for cut surfaces but were ineffective in juice. Ascorbic acid-6-fatty acid esters showed anti-browning activity in juice. Cinnamate and benzoate inhibited browning in juice but induced browning when applied to cut surfaces. Combinations of P-cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 10 publications
4
82
0
1
Order By: Relevance
“…The use of sulfites is one of the most effective methods to prevent enzymatic browning reactions. However, due to the health concerns, there have been great efforts to minimize or eliminate the use of sulfites in food technology; this encouraged the use of sulfite alternatives, such as ascorbic acid and its derivatives, -cyclodextrin, L-cysteine, and 4-hexylresorcinol (1)(2)(3). These chemicals are less effective compared with sulfites and need some complementary treatments such as packaging under nitrogen atmosphere and/or use in combination with heat treatments, acidic solutions, or polyphosphates (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The use of sulfites is one of the most effective methods to prevent enzymatic browning reactions. However, due to the health concerns, there have been great efforts to minimize or eliminate the use of sulfites in food technology; this encouraged the use of sulfite alternatives, such as ascorbic acid and its derivatives, -cyclodextrin, L-cysteine, and 4-hexylresorcinol (1)(2)(3). These chemicals are less effective compared with sulfites and need some complementary treatments such as packaging under nitrogen atmosphere and/or use in combination with heat treatments, acidic solutions, or polyphosphates (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that pre-harvest prevailing conditions such as climate, light, soil type, mulching, fertilization and application of naturally occurring compounds can affect the nature of the antioxidant and antioxidant activity of various fruits (Antalovich et al, 2002). Various researchers have reported Ascorbic acid as effective measure in controlling enzymatic browning of fruits and vegetables (Santerre et al, 1988;Sapers et al, 1989). Various kinds of molds (Fungi) in different nuts that are already roasted can be removed by application of with and ascorbic acid solution along with water (Clark, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since an increase in the concentration of these antioxidants from 10 mM to 50 mM did not show a significant improvement in controlling brown pigments, higher concentrations were not studied. In the case of CD, higher concentrations could not be tested because of the limited solubility of this compound (Sapers et al 1989).…”
Section: Results and Discussion Effect Of Antioxidants On Color And mentioning
confidence: 99%
“…Common technologies used to prevent browning include reduction of temperature, use of modified atmosphere (MA) packaging, and application of compounds that act to inhibit enzyme, remove its substrates or function as preferred substrate . The antioxidants used in fresh-cut fruits and vegetables include acidulants, such as citric, ascorbic, and peracetic acid (CA, AA, and PA) Sapers and Miller 1992;Castañer et al 1996;, reducing agents such as cysteine (Cys) and AA, chelating and complexing agents such as hexametaphosphate (HMP) and ciclodextrin (CD) (Sapers et al 1989;, and enzymatic inhibitors such as 4-hexylresorcinol (Hexyl) (Monsalve-Gonzalez et al 1993; Luo and Barbosa-Cánovas 1997; . Effectiveness of these antibrowning agents depends on many factors, such as commodity, cultivar, concentration and synergy with other antioxidants, pH, application system, etc.…”
Section: Introductionmentioning
confidence: 99%